Importance of the Metal–Oxide Interface in Catalysis: In Situ Studies of the Water–Gas Shift Reaction by Ambient‐Pressure X‐ray Photoelectron Spectroscopy1. Issue 19 (9th April 2013) - Mudiyanselage, Kumudu; Senanayake, Sanjaya D.; Feria, Leticia; Kundu, Shankhamala; Baber, Ashleigh E.; Graciani, Jesús; Vidal, Alba B.; Agnoli, Stefano; Evans, Jaime; Chang, Rui; Axnanda, Stephanus; Liu, Zhi; et al.
<x xml:space="preserve">Abstract</x> Where oxide and metals meet: The activation of an efficient associative mechanistic pathway for the water–gas shift reaction by an oxide–metal interface leads to an increase in the catalytic activity of nanoparticles of ceria deposited on Cu(111) or Au(111) by more than an order of magnitude (see graph). In situ experiments demonstrated that a carboxy species formed at the metal–oxide interface is the critical intermediate in the reaction.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>